Lung function of healthy boys and girls in Jamaica in relation to ethnic composition, test exercise performance, and habitual physical activity - Miller, G. J. (1977)
Miller, G. J., Saunders, M. J., Gilson, R. J. C., and Ashcroft, M. T. (1977).Thorax, 32, 486-496. Lung function of healthy boys and girls in Jamaica in relation to ethnic composition, test exercise performance, and habitual physical activity. The relationships of forced expiratory volume and forced vital capacity on height, age, sex, area of residence, and ethnic composition were assessed in 622 children in Jamaica. Rural children in hill-farming communities were judged to have a higher habitual physical activity than urban children. Allowing for differences in body size, forced vital capacity averaged 3% greater in rural children than in urban children, 7% less in girls than in boys, and 16% greater in children of European origin than in children of African descent. Lung volumes, indices of gas transfer, and submaximal-exercise responses were measured in a subgroup of 108 children of African descent believed to be of common genetic stock. Total lung capacity and vital capacity averaged respectively 6% greater and 7% greater in rural than in urban children of equal height but residual volume and transfer factor did not differ significantly between localities. Rural children had a lower average cardiac frequency during test exercise than did urban children. Sex differences and locality differences in vital capacity and total lung capacity disappeared when allowance was made for standardised exercise cardiac frequency. At standard body size and age transfer factor increased with decreasing cardiac frequency for standard work. The results suggest an harmonious development of the cardiac and respiratory components of the oxygen transport system, consonant with the demand for muscular work. Increased habitual physical activity and improved exercise performance appear to be associated with increases in vital capacity, total lung capacity, and transfer factor.